(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This study looks at how the stepping game can help young learners remember English words. Learning vocabulary is very important for children, but they often forget new words when using normal teaching methods. The stepping game uses movement and fun to make learning easier and more interesting. The study was done with primary school children. In the game, learners stepped on word cards on the floor while listening to instructions, saying the words, or showing their meaning. The teacher watched the class and gave a vocabulary test before and after the game. The results show that the stepping game helped children remember words better and made them more interested in learning. They enjoyed the game and participated more in class. This study suggests that using games with movement is a good way to teach vocabulary to young learners.